Early Cretaceous adakitic rocks in the Anqing region, southeastern China: constraints on petrogenesis and metallogenic significance. Issue 11 (26th October 2018) - Xie, Jiancheng; Wang, Yu; Li, Quanzhong; Liu, Jianmin; Yan, Jun; Sun, Weidong
ABSTRACT: The Anqing region in Lower Yangtze River metallogenic belt is one of the important Cu polymetal producers in China. The origin of Cu polymetallic deposits in the region is closely related to Early Cretaceous adakitic intrusions. To constrain the petrogenetic and metallogenic significance of the adakitic rocks, a detailed geochronological, geochemical, and Sr–Nd–Pb–Hf isotopic study was performed. The Anqing adakitic rocks (SiO2  = 57.4–64.2 wt.%) consist mainly of quartz monzodiorite, formed at 138.2 ± 1.7 Ma (Mean Standard Weighted Deviation (MSWD) = 0.61). They have high MgO, Al2 O3, Sr, and low Rb, Y, Yb contents, together with high Sr/Y (50.5–222) and La/Yb (31.9–46.9) ratios. They also show negative whole-rock ε Nd ( t ) (−9.8 to −8.5) and zircon ε Hf ( t ) (−10.0 to −5.4), and high oxygen fugacity (mainly −17.0 to −8.01) values and radiogenic Pb isotopic compositions with ( 206 Pb/ 204 Pb) i  = 17.692–17.884, ( 207 Pb/ 204 Pb) i  = 15.413–15.511, and ( 208 Pb/ 204 Pb) i  = 37.611–37.943. Coupled with negative Nb–Ta anomalies, low K2 O/Na2 O ratios (0.39–0.62), and high Mg# values (0.44–0.71), these data suggest the adakitic rocks and associated large-scale Cu–Au mineralization of the Anqing region resulted from partial melting of the high oxidized subducted oceanic crust. Addition of mantle-derived magmas and assimilation of crustal materials during emplacement are also possible.